Records Management and Organizational Performance - Paul Chinedu Agu; Emeka Emmanuel Njoku; Shagari Umaru; Nwabueze Ifenyinwa Eleke; Ifeanyi Henry Nwokoma; Okehi Tunde Bashiru (ARRUS Journal of Social Sciences and Humanities, 2022)
This study was carried out on records management and organizational performance in Renaissance University Ugbawka, Enugu State, Nigeria. Specifically, this study sought to find out the relationship between: records keeping and employee effectiveness; document handling and employee performance, as well as adequate records safety and availability of record facilities. The study adopted the survey research design using primary sources of data. Fifty-eight full time academic staff of Renaissance University Ugbawka, Enugu state served as the population of this study, out of which, 47 responses were used for analysis. Again, data were collected and analyzed using tables and simple percentages. Stated hypotheses were tested using Multiple Regression Analysis at 0.05 level of significance in SPSS version 21. The study found positive and significant relationships between record keeping and employee effectiveness and between document handling and employee performance. Statistically speaking, the study did not find any positive and significant relationship between adequate records safety and availability of facilities. Thus, the study concluded that proper records keeping helps to avert the stress of duplicating recording efforts, saves time used in recreating such records and enables users to compare performance over time, thereby improving employee effectiveness. Again, when organizations properly handle their records, staff achieve greater results by working in line with the records policies; records become easier to handle and the staff utilize their recording time effectively, thereby improving employee performance. In addition, adequate safety of organizational records enables proper identification and location of records, easy access to records by users and accountability among staff.